Rethinking ressentiment: democratic and urban implications - Carrera, Letizia (Frontiers in Sociology, 2025)
The article explores the complex interplay between resentment and democratic society, and the material and visible forms that this emotion takes within the city. Ressentiment emerge as key explanatory categories, influencing individuals’ perceptions and actions within social processes. Resentment is portrayed as a deeply democratic sentiment, arising from the perceived betrayal of the promise of equality inherent in democratic ideals. The article examines how this perceived injustice fuels a pervasive sense of resentment, which can either fragment social bonds or, alternatively, serve as a catalyst for political and social change. Urban space, with its dense and heterogeneous environment, is identified as a critical site where these dynamics become particularly visible. Cities, as synecdoche of society, not only reflect but actively shape social processes and collective feelings. They are arenas where perceived inequalities can either lead to social envy and resentment or foster solidarity and transformative activism. The article argues that addressing the roots and manifestations of resentment through inclusive and participatory processes is crucial for mitigating its destructive potential and harnessing it for positive social change. This approach involves creating urban spaces that facilitate critical reflection, social interaction, and collective action, thereby strengthening social and political efficacy among individuals and communities.